Thermal Analysis and Structural Characterization Studies of Calcite Mineral at Different Microns - Renuga Devi, T.S.; Gayathri, S. (Asian Journal of Chemistry, 2015)
Thermal analysis methods provide convenient method for quantification study of minerals, which is of great importance in various industries. Intensive studies have been made over years for calcite mineral obtained from mining area as such. In present work, the effect of particle size towards decomposition process of calcite mineral is studied using three particle size ranges which are 125, 50 and 25 mu. Decomposition reactivity is conducted using thermal gravimetric analyzer at heating rate of 20 °C/min in inert nitrogen atmosphere. Structural investigation using X-ray diffraction shows calcite is made up of 75 % calcium element and CaO is produced after decomposition is conducted, which is also been analyzed by X-ray diffusivity analyzer. The chemical composition is unaltered for different size. No structural variation for various particle sizes. Decomposition rate increased as the particle size is larger. The sample with smallest particle size exhibits to have minimum decomposition rate among the other sizes. It occurred at 811 °C with decomposition rate of 0.066/min. It is also observed that the time taken for decomposition of smallest particle size is shorter compared to the sample with larger particle size. Particle size really becomes a factor to the thermal decomposition process as it determines the surface area of the sample. Besides, smallest particle size exhibits the minimum decomposition rate. To conclude, calcite is a promising source for CaO and based on three different particles sizes used, sample at maximum size offers the highest decomposition rate.